Inference on germline BAP1 mutations and asbestos exposure from the analysis of familial and sporadic mesothelioma in a high‐risk area. Issue 1 (18th September 2014) - Betti, Marta; Casalone, Elisabetta; Ferrante, Daniela; Romanelli, Antonio; Grosso, Federica; Guarrera, Simonetta; Righi, Luisella; Vatrano, Simona; Pelosi, Giuseppe; Libener, Roberta; Mirabelli, Dario; Boldorini, Renzo; et al.
<x xml:space="preserve">Abstract</x> Inherited loss‐of‐function mutations in the BAP1 oncosuppressor gene are responsible for an inherited syndrome with predisposition to malignant mesothelioma (MM), uveal and keratinocytic melanoma, and other malignancies. Germline mutations that were inherited in an autosomal dominant fashion were identified in nine families with multiplex MM cases and 25 families with multiple melanoma, renal cell carcinoma, and other tumors. Germline mutations were also identified in sporadic MM cases, suggesting that germline mutations in BAP1 occur frequently. In this article, we report the analysis of BAP1 in five multiplex MM families and in 103 sporadic cases of MM. One family carried a new truncating germline mutation. Using immunohistochemistry, we show that BAP1 is not expressed in tumor tissue, which is in accordance with Knudson's two hits hypothesis. Interestingly, whereas the three individuals who were possibly exposed to asbestos developed MM, the individual who was not exposed developed a different tumor type, that is, mucoepidermoid carcinoma. This finding suggests that the type of carcinogen exposure may be important for the cancer type that is developed by mutation carriers. On the contrary, the other families or the 103 sporadic patients did not show germline mutations in BAP1. Our data show that BAP1 mutations are very rare in patients with sporadic MM, and we report a new BAP1 mutation, extend the cancer types associated with these mutations, and suggest the existence of other yet unknown genes in the pathogenesis of familial MM. © 2014 Wiley Periodicals, Inc.